Near‐fatal Intoxication with the “New” Synthetic Opioid U‐47700: The First Reported Case in the Czech Republic - Židková, Monika; Horsley, Rachel; Hloch, Ondřej; Hložek, Tomáš (Journal of forensic sciences, 2019)
Recreational use of the potent synthetic opioid 3,4‐ dichloro‐N‐(2‐(dimethylamino)cyclohexyl)‐N‐methylbenzamide (U‐47700) is rising, accompanied by increasingly frequent cases of serious intoxication. This article reports a case of near‐fatal U‐47700 intoxication. A man was found unconscious (with drug powder residues). After 40 h in hospital (including 12 h of supported ventilation), he recovered and was discharged. Liquid chromatography/high‐resolution mass spectrometry (LC/HRMS) or gas chromatography/mass spectrometry (GC/MS) were used to detect and quantify substances in powders, serum and urine. Powders contained U‐47700 and two synthetic cannabinoids. Serum and urine were positive for U‐47700 (351.0 ng/mL), citalopram (<LOQ), tetrahydrocannabinol (THC: 3.3 ng/mL), midazolam (<LOQ) and a novel benzodiazepine, clonazolam (6.8 ng/mL) and their metabolites but negative for synthetic cannabinoids. If potent synthetic opioids become cheaper and more easily obtainable than their classical counterparts (e.g., heroin), they will inevitably replace them and users may be exposed to elevated risks of addiction and overdose.